Analisis Tingkat Service level Warehouse Dalam Manajemen Persediaan Barang Pada PT X Cabang Bekasi - Rahma, Dyah Calystha; Auliana, Lina; Novel, Nurillah Jamil A (JURNAL TERAPAN MANAJEMEN DAN BISNIS, 2024)
This study aims to analyze the causes of the low warehouse service level and the increase in out of stock incidents at PT X Bekasi Branch. Based on the problems identified, PT X's service level has, at times, fallen below 85%, which is under the company’s management target. Several key items were also identified in this study as having warehouse service levels lower than those from the supplier. The research focuses on four main factors: Place, Product, People, and Process. The findings indicate that the most dominant factor is product, specifically when warehouse stock runs out before the next shipment from the supplier arrives. This issue is worsened by inadequate stock monitoring by the warehouse team in submitting requests to the PKM DC. The place factor, related to limited storage space, is not a significant obstacle due to stable inventory turnover. Meanwhile, the process factor shows that delivery schedules that do not align with purchase orders (POs) disrupt the inventory flow. As a solution, several action plans were developed, such as applying the Safety Stock and Reorder Point methods, improving daily stock monitoring, enhancing coordination with suppliers, and optimizing warehouse layout. These measures are expected to improve service levels, reduce OOS, and support smoother branch operations.